The microbial load with genital mycoplasmas correlates with the degree of histologic chorioamnionitis in preterm PROM - Kacerovsky, Marian; Pliskova, Lenka; Bolehovska, Radka; Musilova, Ivana; Hornychova, Helena; Tambor, Vojtech; Jacobsson, Bo (American journal of obstetrics and gynecology, 2011)
OBJECTIVE: We sought to determine whether there is an association between bacterial load of genital mycoplasmas and histologic chorioamnionitis (HCA) in women with preterm premature rupture of membranes (PPROM). STUDY DESIGN: A total of 103 women with PPROM between 24-36 weeks of gestation were included in the study. Amniocenteses were performed, and the amounts of target genital mycoplasma DNA in amniotic fluid samples were evaluated using real-time polymerase chain reaction. The bacterial load of the genital mycoplasmas was relatively assessed using the threshold cycle value. RESULTS: The presence of genital mycoplasmas in amniotic fluid was found in 38% (39/103) of the women. The presence of HCA was associated with lower threshold cycle values (median 21.3, interquartile range, 16.5-28.5, vs median 29.4, interquartile range, 27.0-30.5; P = .005). CONCLUSION: HCA in PPROM is associated with a higher bacterial load of genital mycoplasmas.
Keywords: Mycoplasma Infections; Mycoplasma; mykoplazmové infekce; předčasný odtok plodové vody; plodová voda; Bacterial Load; Chorioamnionitis; Pregnancy; těhotenství; Adult; Prospective Studies; dospělí; Fetal Membranes, Premature Rupture; Amniotic Fluid; chorioamnionitida; lidé; ženské pohlaví; Humans; Female; bakteriální nálož; prospektivní studie